PENGARUH MEDIA PEMBELAJARAN WORDWALL TERHADAP HASIL BELAJAR IPAS PESERTA DIDIK KELAS IV SDN PUCANG 4 SIDOARJO - Avina Salsabilatun Nabila; Ana Christanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low learning outcomes of fourth-grade students in the science of flora and fauna distribution material due to the limited use of interactive learning media. This study aims to determine the effect of the use of Wordwall learning media on the learning outcomes of fourth-grade students of SDN Pucang 4 Sidoarjo. The study used a quantitative approach with a One Group Pretest–Posttest design. The subjects of the study were fourth-grade students of SDN Pucang 4 Sidoarjo. Data collection techniques were carried out through Pretest and Posttest tests to measure student learning outcomes before and after treatment. Treatment was given through the use of Wordwall media on the distribution of flora and fauna material for three meetings. The results of the study showed an increase in student learning outcomes after the use of Wordwall media in science learning. Thus, Wordwall learning media has a positive effect on the learning outcomes of fourth-grade students of SDN Pucang 4 Sidoarjo.